If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + 10 = 4t + -50 Reorder the terms: 10 + 2t = 4t + -50 Reorder the terms: 10 + 2t = -50 + 4t Solving 10 + 2t = -50 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 10 + 2t + -4t = -50 + 4t + -4t Combine like terms: 2t + -4t = -2t 10 + -2t = -50 + 4t + -4t Combine like terms: 4t + -4t = 0 10 + -2t = -50 + 0 10 + -2t = -50 Add '-10' to each side of the equation. 10 + -10 + -2t = -50 + -10 Combine like terms: 10 + -10 = 0 0 + -2t = -50 + -10 -2t = -50 + -10 Combine like terms: -50 + -10 = -60 -2t = -60 Divide each side by '-2'. t = 30 Simplifying t = 30
| -8x+-21= | | 4(3x+11)=2.8(16+4x) | | 2-m/21 | | 8x+-21= | | -2x-6=6+2x | | k/-10=3 | | 2t-10=4t-50 | | x*x+38=2x | | 2/3t-9 | | 14g-4=2(7g-2) | | -8x+10+11= | | 4(3x+11)=2.35(16+4x) | | 6x-8x+6=-4x | | 4(3x+11)=2.45(16+4x) | | 1=r/25 | | 5+8(y-4)=5(y+2)-y | | 180(n-2)/n | | [2c+6]+3[c+8]= | | 4+3(x-2)=20 | | 4(3x+11)=3.666(16+4x) | | 4(3x+11)=-3.6(16+4x) | | (X)=2x-7 | | 6n+7-2n-14=4n+18 | | .50(40)=(40-m)+0.80m | | 3(x+1)-2(3x-1)=5(x-2)+7 | | 3x^2+14x-192=0 | | 4(3x+11)=19(16+4x) | | 4(3x+11)=x(16+4x) | | H=5+10t-5t^2 | | -5h=2/2 | | 14x+6=16x | | 24n^2+6n=0 |